#2**+11 **

Alan has an interesting approach.......mine is a little different........but it should still work out the same...

Let's divide the original equation by 4....so we have

x^2 + x + y^2 - 4y - 127/4 =0 add 127/4 to both sides

x^2 + x + y^2 - 4y = 127/4 now, complete the sqaure on x and y

(x^2 + x + 1/4) + (y^2 - 4y + 4) = 127/4 + 1/4 + 4 simplifying, we have

(x + 1/2)^2 + (y - 2)^2 = 144/4

(x + 1/2)^2 + (y - 2 )^2 = 36

So. the center is (-1/2, 2) and the radius is 6

CPhill
Jul 10, 2014

#2**+11 **

Best Answer

Alan has an interesting approach.......mine is a little different........but it should still work out the same...

Let's divide the original equation by 4....so we have

x^2 + x + y^2 - 4y - 127/4 =0 add 127/4 to both sides

x^2 + x + y^2 - 4y = 127/4 now, complete the sqaure on x and y

(x^2 + x + 1/4) + (y^2 - 4y + 4) = 127/4 + 1/4 + 4 simplifying, we have

(x + 1/2)^2 + (y - 2)^2 = 144/4

(x + 1/2)^2 + (y - 2 )^2 = 36

So. the center is (-1/2, 2) and the radius is 6

CPhill
Jul 10, 2014